The Implementation of Wordwall as a Learning Medium to Enhance Arabic Learning Motivation Among Fourth Grade Students - Susilowati, Retno; Sa'diyah, Zaimatus; Islahuddin; Noviana, Irma (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to analyze the implementation of Wordwall as a learning medium to improve the learning motivation of fourth-grade students in the Arabic language subject at MI Darus Sa’adah. Based on field data, it was found that students faced difficulties in learning Arabic because it is a foreign language, which consequently led to low motivation and enthusiasm for learning. This research employed a qualitative descriptive approach with a focus on the theme of Indonesian cultural diversity, delivered through interactive activities using Wordwall.The results revealed that the use of Wordwall significantly influenced students’ engagement and enthusiasm. Before the implementation, only six students actively participated in the learning process; after using Wordwall, 14 students showed increased motivation and enthusiasm for learning. Students’ level of motivation improved, as evidenced by their enthusiasm during the learning activities and their mastery of the material at the end of the lesson.This study highlights two crucial stages in the implementation process: (1) the planning stage, which includes analyzing students’ needs and designing appropriate learning media for Arabic lessons, and (2) the classroom implementation stage, where the game-based and interactive features of Wordwall encouraged active participation and fostered a positive learning environment. These findings indicate that Wordwall is an effective and feasible learning medium to enhance students’ motivation in learning Arabic at the madrasah ibtidaiyah level.